COMPARATIVE ANALYSIS OF ENGLISH AND KARAKALPAK PROVERBS AND SAYINGS ABOUT “LABOR” - Uzaqbergenova , Durdana (Educational Research in Universal Sciences, 2023)
The article deals with investigated field of Karakalpak and English folk genre as proverbs. The article goes through to find out distinguishes, similarities of Englishand Karakalpak proverbs.